The relationship between public health expenditure and urban economic resilience - Chen, Erdong; Zhang, Huaxin (Frontiers in Public Health, 2025)
Achieving urban economic resilience is a critical objective for sustainable development in the face of external shocks. Public health expenditure plays a pivotal role in enhancing urban economic resilience by improving health outcomes, optimizing resource allocation, and strengthening economic capacity to withstand risks. However, the mechanisms through which public health expenditure influences resilience, as well as its regional variations, remain underexplored. This study utilizes panel data from 284 cities in China spanning from 2008 to 2021, constructing an econometric model that incorporates mediating variables such as technological innovation and per capita GDP, to assess both the direct and indirect effects of public health expenditure on urban economic resilience. Additionally, spatial econometric models are employed to further analyze the spatial spillover effects of public health expenditure. The findings reveal that public health expenditure significantly enhances urban economic resilience, with technological innovation and per capita GDP serving as key mediating pathways. Regional analysis shows that the impact is most pronounced in eastern cities, followed by central cities, while the effect in western cities is weaker and, in some cases, negative. Spatial analysis further indicates that public health expenditure has a significant positive spillover effect on neighboring cities, primarily through resource sharing and technology diffusion. This study suggests that optimizing the structure of public health expenditure, increasing infrastructure investment, supporting non-capital and resource-dependent cities, and promoting digital healthcare and regional cooperation are essential to enhancing economic resilience, fostering high-quality urban development, and advancing regional equity.